2006
DOI: 10.1176/ajp.2006.163.9.1594
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Putamen D 2 Receptor Binding Potential in Major Depression With Motor Retardation: An [ 11 C]Raclopride Positron Emission Tomography Study

Abstract: The results argue that extracellular dopamine is lower in subjects experiencing a major depressive episode that features motor retardation. This depression subtype should preferentially benefit from dopamine-increasing medications and should be targeted in future clinical trials of dopamine reuptake inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 40 publications
4
119
4
Order By: Relevance
“…Our findings of lower D 2/3 receptor BP ND in depression contrast, however, with reports of higher (D'haenen and Bossuyt, 1994;Meyer et al, 2006;Shah et al, 1997) or equivalent (Ebert et al, 1996;Parsey et al, 2001) striatal D 2/3 receptor BP ND in the whole striatum of depressed subjects relative to controls. It remains unclear how these data compare with ours; however, these studies did not discriminate the AVS from the remainder of the striatum, and the differences we identified were maximal in the ventral striatum.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings of lower D 2/3 receptor BP ND in depression contrast, however, with reports of higher (D'haenen and Bossuyt, 1994;Meyer et al, 2006;Shah et al, 1997) or equivalent (Ebert et al, 1996;Parsey et al, 2001) striatal D 2/3 receptor BP ND in the whole striatum of depressed subjects relative to controls. It remains unclear how these data compare with ours; however, these studies did not discriminate the AVS from the remainder of the striatum, and the differences we identified were maximal in the ventral striatum.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the results of some of these previous studies were confounded by recent exposure to psychotropic drugs. Finally, several prior studies were in hospitalized or psychomotorically retarded depressives (Ebert et al, 1996;Meyer et al, 2006;D'haenen and Bossuyt, 1994), and several reported positive correlations between D 2/3 receptor BP ND and ratings of psychomotor slowing (Meyer et al, 2006;Shah et al, 1997). Such patients may have had lower dopaminergic tone or lower intrasynaptic DA concentrations in the dorsal striatal regions that subserve motor processing, which putatively may result in compensatory increases in D 2/3 receptor expression or affinity, or in reduced competition for binding to [ 11 C]raclopride or [ 123 I]-iodobenzamide, which are sensitive to endogenous DA levels (Laruelle, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dopamine D 1 receptors were assessed by [ 11 C]SCH 23,390 or [ 11 C]NNC-112 in two PET studies of depression (Dougherty et al 2006;Cannon et al 2008), and both reports found less binding in striatal regions of depressed subjects than of healthy controls. Dopamine D 2/3 receptors www.intechopen.com have been assessed in five PET studies using either [ 11 C]raclopride or [ 11 C]FLB 457 in depressed subjects and healthy controls; one study noted more striatal binding by dopamine D 2/3 receptors in depressed subjects (Meyer et al 2006b), another study found less dopamine D 2/3 receptor binding in depression (Montgomery et al 2007), and three studies showed no difference between depressed and healthy subjects in dopamine D 2/3 receptor binding in brain regions (Kuroda et al 2006;Montgomery et al 2007;Busto et al 2009). The transport of dopamine as well as noradrenaline from the synaptic cleft into presynaptic terminals was assessed by PET using [ 11 C]RTI-32 in 20 Parkinson patients, some of which were depressed (Remy et al 2005).…”
Section: Recent Pet Studies Of Dopamine In Depressive Disordersmentioning
confidence: 99%